2010
DOI: 10.1099/vir.0.025791-0
|View full text |Cite
|
Sign up to set email alerts
|

A PSAP motif in the ORF3 protein of hepatitis E virus is necessary for virion release from infected cells

Abstract: We have previously demonstrated that the release of hepatitis E virus (HEV) from infected cells depended on ORF3 protein, which harbours one or two PSAP motifs. To elucidate the PSAP motif(s) in the ORF3 protein during virion egress, five PSAP mutants derived from an infectious genotype 3 cDNA clone of pJE03-1760F/wt that can grow efficiently in PLC/PRF/5 cells were analysed. Four mutants, including mutLSAP, mutPSAL, mutLSAL (the substituted amino acids in the authentic PSAP motif are underlined) and mutPLAP/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
151
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(163 citation statements)
references
References 35 publications
9
151
1
2
Order By: Relevance
“…The PSAP motif between amino acid residues 95 and 98 of the ORF3 protein was found to be conserved among all known HEV strains of genotypes 1-4 and avian HEV strains (Nagashima et al, 2011 As shown in Fig. 1(a), the expression of Tsg101-Myc was detectable by Western blotting analysis using anti-Myc mAb (left panel) and anti-Tsg101 mAb (right panel).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…The PSAP motif between amino acid residues 95 and 98 of the ORF3 protein was found to be conserved among all known HEV strains of genotypes 1-4 and avian HEV strains (Nagashima et al, 2011 As shown in Fig. 1(a), the expression of Tsg101-Myc was detectable by Western blotting analysis using anti-Myc mAb (left panel) and anti-Tsg101 mAb (right panel).…”
Section: Introductionmentioning
confidence: 88%
“…The ORF2 protein is the viral capsid protein of 660 aa, while the ORF3 protein is a small protein of only 113 or 114 aa, which has been suggested to act as an adaptor to link the intracellular transduction pathways, reduce the host inflammatory response and protect virus-infected cells (Chandra et al, 2008). Recently, it was demonstrated that the ORF3 protein is important for egress from cultured cells (Emerson et al, 2010;Nagashima et al, 2011;Yamada et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the PSAP motif plays an important role as a functional domain for HEV budding. 79 Similar role of the PSAP motif in virus release have been shown in vivo in chickens and not in chicken liver cell line expressing pORF2. 80 pORF3 was initially predicted to express as 123 aa long polypeptide.…”
mentioning
confidence: 74%